2003
DOI: 10.1051/vetres:2003006
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bovine soluble CD14 reduces severity of experimental Escherichia coli mastitis in mice

Abstract: -Endotoxin, or lipopolysaccharide (LPS), is responsible for pathogenesis of infections induced by Gram-negative bacteria, such as E. coli. The cellular response to LPS is modulated by interactions among LPS, LPS-binding protein (LBP) and CD14. Accumulated evidence shows that the soluble form of CD14 (sCD14) competes with membrane-bound CD14 (mCD14) for LPS and plays a pivotal role in regulating bacterial infection and septic shock caused by Gram-negative bacteria. Recombinant bovine sCD14 (rbosCD14) was produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Sordillo and Nickerson, 1986). The murine model for the study of bovine mastitis has also been utilized to evaluate the efficacy of numerous vaccines (Mamo et al, 2000;Gomez et al, 2002), antimicrobials (Brouillette et al, 2004) and immunomodulatory compounds (Sordillo and Nickerson, 1986;Lee et al, 2003;Boulanger et al, 2007) in order to elucidate agents that might prevent or treat bovine mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…Sordillo and Nickerson, 1986). The murine model for the study of bovine mastitis has also been utilized to evaluate the efficacy of numerous vaccines (Mamo et al, 2000;Gomez et al, 2002), antimicrobials (Brouillette et al, 2004) and immunomodulatory compounds (Sordillo and Nickerson, 1986;Lee et al, 2003;Boulanger et al, 2007) in order to elucidate agents that might prevent or treat bovine mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…An array of experimental approaches, including the use of LBP -/- [14,20] or CD14 -/- [65] mice, CD14 neutralizing antibodies [25,63], and administration of exogenous LBP [24] have established a protective role for CD14 and LBP in mediating host responses to LPS and Gram-negative bacterial infection. We have shown that exogenous recombinant bovine sCD14 enhances intramammary clearance of E. coli in both mice [26] and cattle [27]. CD14 and LBP have further been shown to facilitate TLR-2 activation by lipoteichoic acid and peptidoglycan derived from Gram-positive bacteria [48,66].…”
Section: Discussionmentioning
confidence: 99%
“…Following intramammary LPS infusion, sCD14 increases in milk Lee et al, 2003a), paralleled by an increase in LBP . Moreover, sCD14 has been shown to sensitize the mammary gland to LPS (Wang et al, 2002) and to reduce the severity of experimental E. coli mastitis in mice (Lee et al, 2003c) and cows (Lee et al, 2003b). Interestingly, maximal levels of the chemoattractant IL-8 and complement component 5a (C5a) were observed before increases in either milk LBP or sCD14.…”
Section: Introductionmentioning
confidence: 99%